Short dogmatic analysis of the crime of extortion in the Penal Code for the State of Puebla, México (2023)
This paper examines the elements of the crime of extortion in the criminal legislation of the State of Puebla, Mexico. This way, we begin with the study of the protected juridical values. Then, we determine the typical conduct, which has to be impregnated with bad intention, but specially, with the two subjective specific elements of willfulness that characterize it. All this without failing to consider the broad commissive means in which this type of crime can be executed. It ends with the study of the punishment and its aggravating circumstance. And, in that sense, it should be noted that the latter is closely related to a specific condition in the perpetrator of the crime, who, using it, must implement that criminal behavior.